2009
DOI: 10.1387/ijdb.072556cc
|View full text |Cite
|
Sign up to set email alerts
|

Reptile scale paradigm: Evo-Devo, pattern formation and regeneration

Abstract: The purpose of this perspective is to highlight the merit of the reptile integument as an experimental model. Reptiles represent the first amniotes. From stem reptiles, extant reptiles, birds and mammals have evolved. Mammal hairs and feathers evolved from Therapsid and Sauropsid reptiles, respectively. The early reptilian integument had to adapt to the challenges of terrestrial life, developing a multi-layered stratum corneum capable of barrier function and ultraviolet protection. For better mechanical protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
129
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 115 publications
(170 reference statements)
1
129
0
Order By: Relevance
“…The coexistence of scaly skin and bristle-like integumentary structures has been reported for other non-avian dinosaursalbeit not theropods (e. g., Psittacosaurus; MAYR et al 2002) -but it remains highly unusual. Nonetheless, such coexistence is not at odds with a wealth of laboratory experiments that have demonstrated that small groups of stem cells in scales can be stimulated by molecular perturbation to form active feather follicles that develop feathers (DHOUAILLY et al1980;WIDELITZ et al 2000WIDELITZ et al , 2003CHANG et al 2009). In fact, such "feathery scales" are regularly envisioned as an intermediate stage of models of feather evolution (CHANG et al 2009).…”
Section: Soft Tissuementioning
confidence: 99%
“…The coexistence of scaly skin and bristle-like integumentary structures has been reported for other non-avian dinosaursalbeit not theropods (e. g., Psittacosaurus; MAYR et al 2002) -but it remains highly unusual. Nonetheless, such coexistence is not at odds with a wealth of laboratory experiments that have demonstrated that small groups of stem cells in scales can be stimulated by molecular perturbation to form active feather follicles that develop feathers (DHOUAILLY et al1980;WIDELITZ et al 2000WIDELITZ et al , 2003CHANG et al 2009). In fact, such "feathery scales" are regularly envisioned as an intermediate stage of models of feather evolution (CHANG et al 2009).…”
Section: Soft Tissuementioning
confidence: 99%
“…conidiation | stress | transcriptome T he study of responses to mechanical damage has implications for medical applications related to tissue regeneration and repair (1). A conserved defense mechanism is present in plants and animals, in which the production of reactive oxygen species (ROS) and lipid metabolism are essential to the response (2).…”
mentioning
confidence: 99%
“…However, geckos are part of a lineage of tetrapods (sauropsids) whose success in dealing with desiccating terrestrial environments has involved many modifications to the skin (Chang et al, 2009). Gecko skin is actually a complex, dynamic, heterogeneous, multi-layered material, and there is evidence that lipids (fat) and proteins are both present at the contact interface (Alibardi et al, 2011;Hsu et al, 2012).…”
Section: Down and Dirtymentioning
confidence: 99%